2019
DOI: 10.1097/brs.0000000000002805
|View full text |Cite
|
Sign up to set email alerts
|

Increased Proportion of Fusion Surgery for Degenerative Lumbar Spondylolisthesis and Changes in Reoperation Rate

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
1
19
1
Order By: Relevance
“…Multiple regression analysis indicated that the change in DH and fusion SL was positively correlated with changes in ODI and VAS scores, respectively, consistent with the findings of previous studies [32]. While previous studies observed a change in sagittal balance at least 2 years after surgery [33,34], we observed similar outcomes in a mean follow-up period of only 6 months. This improvement might be due to better distraction of the intervertebral space, which maintains the stability of the lumbar spine and is conducive to the improvement of clinical effects.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple regression analysis indicated that the change in DH and fusion SL was positively correlated with changes in ODI and VAS scores, respectively, consistent with the findings of previous studies [32]. While previous studies observed a change in sagittal balance at least 2 years after surgery [33,34], we observed similar outcomes in a mean follow-up period of only 6 months. This improvement might be due to better distraction of the intervertebral space, which maintains the stability of the lumbar spine and is conducive to the improvement of clinical effects.…”
Section: Discussionsupporting
confidence: 91%
“…A recent RCT [41] and systematic review [42] also recommended decompression alone for LSS with degenerative spondylolisthesis. There is the opinion that the increased proportion of fusion surgery without improvement in the probability of reoperation in an aging society may be cautiously addressed in deciding future health policies [43]; therefore, minimally invasive lumbar decompression surgery should be considered for LSS with or without degenerative spondylolisthesis. The management of LSS with degenerative deformity is complicated by this consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery with general anesthesia for the lumbar spine remains challenging. Multiple factors, including old age, osteoporosis and other unfavorable factors, may lead to a poor clinical outcome (20). Furthermore, residual axial lower back pain and adjacent-segment degeneration after instrument implantation are commonly indicated in a number of patients (21).…”
Section: Discussionmentioning
confidence: 99%